Provision Of Fish Steak And Color Fruit Service In Increasing Iron And Hemoglobin Levels Patients Of Hiv/Aids - Dwi Handayani; Iskandar Markus Sembiring (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2022)
HIV (Human Immunodeficiency Virus) is a microorganism in the form of a virus that enters the human body that attacks the immune system so that it weakens the body's ability to fight diseases. To overcome the problem of anemia in HIV patients, additional foods can be given that contain high protein, iron (Fe), Zn and vitamin C which can help absorb iron, one of which is the provision of cork fish steak which is used as a snack or snack and juice. colored fruit juice. Giving snakehead fish steak combined with colored fruit juice has the potential to increase iron and hemoglobin levels in HIV/AIDS sufferers to reduce anemia. This study aims to determine the effect of giving snakehead fish steak and colored fruit juice to increase iron (Fe) and hemoglobin (Hb). This study uses a quantitative method with the type of Pre-Experiment which is designed in a one group pre-test post-test design and the population is all 20 inpatients. The results of the paired t-test obtained p-value = 0.000. The conclusion is that there is an effect of giving snakehead fish steak and colored fruit juice to increase iron (Fe) and hemoglobin (Hb). It is recommended for people with HIV/AIDS who have problems with low levels of iron (Fe) in the blood and hemoglobin (Hb) in order to take advantage of snakehead fish steak as food/snack and colored fruit juice as a drink. So that way, people with HIV / AIDS can always be fresh and fit in carrying out activities in their lives.